EKSPRESI BUDAYA PADA PERAN DAN KEDUDUKAN BUNDO KANDUANG DALAM NOVEL-NOVEL WARNA LOKAL MINANGKABAU ERA REFORMASI - Erizal Gani; Zulfikarni Zulfikarni (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
The research is carried out to describe the role and position of bundo kandung as woman who was instrumental in the formation of the next generation character in the local Minangkabau’s novels during the new order. The research uses qualitative description method , and content analysis approach. The result shows that the role and position of women as bundo kandung have been carried out well enough both as a wife and a mother. However, some might just take advantage materially from spouses in which the women or wives cannot stay when things go wrong in their family. Even so, the role of women as bundo kandung is shown through Rumah Mande attitude in taking care of their brother’s children. In the novel, Persiden, bundo kandung is supposed to be taken into account of the Minangkabau tradition. But, their position does not work as it is. The reason for this is men who get the title as penghulu or mamak hold more power than bundo kandung does. Rinnai Kabut Singgalang also shows that bundo kanduang’s authority is getting lessened in the eyes of Minangkabau community. Bundo is simply a people’s symbol, but not to own full rights in the formation personality children and children in his family. The novel Mengurai Rindu describes women as bundo kandung have a great responsibility for their family, community, and husband’s community. In this novel visible that women are not only responsible for the formation of children’s personality, but is also able to protect her husband’s family.